Humoral immunity, vaccination period and demographic characteristics of first immunized smallpox vaccine recipients - O. S. Ermilova; Z. I. Gin’ko; V. A. Belyavskaya (Инфекция и иммунитет, 2021)
General vaccination of population with vaccinia virus leaded to the eradication of smallpox, then it was finished because of the danger of adverse events. The recurrence of research interest in smallpox vaccine is due to the research of using the virus as a weapon of bioterrorism and the increased frequency of orthopoxvirus infections whereas the population immunity decline. The vaccinia virus is also used as a vector for creating recombinant vaccines. Understanding the pathway and predicting the immune response it will be able to avoid possible adverse events and excessive immunization. The aim of the study was to assess the correlations between humoral immunity, clinical signs during a vaccination period, sex and age characteristics of adults who had received several doses of vaccinia virus. We studied a vaccination clinical data of 135 subjects revaccinated with a smallpox vaccine from twice to 10 times. A total of 95% and 5% vaccine recipients experienced mild or moderate vaccination period, respectively. Inoculation skin lesions was noted at 127 subjects (94.1%). Among them more than 22% vaccine recipients experienced local or systemic adverse events. Compared to mild group moderate group had larger hyperemia (p = 0.04), scab (p = 0.01), healing time (p = 0.001). The age subjects with a moderate vaccination period is less than mild (p = 0.03), the chance of lymphadenopathy development is higher within moderate vaccination period (p < 0.001). Vaccinia neutralizing antibody titers were determined for 54 subjects using plaque reduction neutralization tests. There was a noted tendency of higher protective antibody values at women compared with men. Negative correlation between the antibody titers and the hyperemia size was revealed. Frequently axillary adenopathy is assotiated with higher protective antibody values. Vaccinia neutralizing antibody titers value are not associated with the presence and size of the lesion, the scab falling time, age and the number of previous vaccinations. The clinical variability and the immune response using the same vaccine and the same pattern vaccination would be explained by individual genetic differences that should be further explored.